Impacts of land use intensification on human wellbeing: Evidence from rural Mozambique. (November 2019) - Smith, Harriet Elizabeth; Ryan, Casey M.; Vollmer, Frank; Woollen, Emily; Keane, Aidan; Fisher, Janet A.; Baumert, Sophia; Grundy, Isla M.; Carvalho, Mariana; Lisboa, Sá N.; Luz, Ana C.; Zorrilla-Miras, Pedro; et al.
Highlights: Improvements in wellbeing coincided with higher rates of land use intensification with smallholder commercial and subsistence agricultural expansion. No changes to wellbeing were observed with the intensification of charcoal production. Improvements in the wellbeing of the poorest were only found under circumstances of higher market integration. Sustainable and inclusive markets were required alongside land use intensification to improve wellbeing for all households. We advocate for broader framings for land use intensification, to reflect smallholder-dominated landscapes and critically engage with discussions around sustainable development. Abstract: Intensifying land use is often seen as a corollary of improving rural livelihoods in developing countries. However, land use intensification (LUI) frequently has unintended impacts on ecosystem services (ES), which may undermine the livelihoods of the same people who could benefit from intensification. Poorer households are disproportionately dependent on ES, so inequalities may also rise. A disaggregated analysis of LUI is thus fundamental to better understand how LUI can progress in an equitable manner. Using a suite of multi-scale, multidisciplinary social-ecological methods and operationalising multidimensional concepts of land use intensity and wellbeing, we examine three case studies in rural Mozambique. Drawing on interviews, focus group discussions, 1576 household surveys and geospatial data from 27 Mozambican villages, we assess how wellbeing and inequality change with three common LUI pathways: transitions to smallholder commercial crop production, charcoal production, and subsistence expansion. Wellbeing improved with intensification of smallholder commercial and subsistence agriculture, inequality did not change. Unsustainable intensification of charcoal production showed no overall effect on either wellbeing or inequality. Improvements in wellbeing amongst the poorest households were only found with intensification of commercial crop production, where villages had better access to markets. Our findings suggest that socioeconomic benefits from agricultural intensification and expansion may overcome localised environmental trade-offs, at least in the short term. However, unsustainable charcoal resource management and limited productive investment opportunities for rural households resulted in both reduced market access and limited wellbeing improvements. Sustainable and inclusive markets are therefore crucial developments alongside LUI to sustain wellbeing improvements for all households, to ensure that no one is left behind.